EFL STUDENTS’ PERCEPTION ON PLAGIARISM IN HIGHER EDUCATION: TRIGGERING FACTORS AND AVOIDING STRATEGIES - Safrul Muluk; Habiburrahim Habiburrahim; Muhammad Safwan Safrul (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
This study was aimed to examining EFL students’ perception towards plagiarism, factors triggering students to plagiarize in completing their undergraduate theses and their strategies in avoiding plagiarism. The study, conducted at English Language Education Department, in one of the universities in Indonesia, employed a qualitative method approach aiming at getting more information and a detailed description of social or human issues. Ten alumni who were randomly selected agreed to participate in this study. Selected participants were interviewed to collect required information needed to address research questions of this study. Besides interviewing the students, the researchers also analyzed their theses in order to examine the level of plagiarism by using Turnitin software, the result of which showed that the range of similarities index in students’ theses varied from 16 to 36 %. The findings of the study revealed that there were three strategies that students implemented to avoid plagiarism; paraphrasing and quoting others' ideas, understanding the meaning of plagiarism, and using the lectures' particular method and online plagiarism detection software. Furthermore, the study found that the factors influencing students to plagiarize were related to time limitation on an assignment and poor time management, ease of using online sources, lack of understanding to plagiarism, and poor understanding of plagiarism acts.